Investigation of thermodynamic properties of Amine Modified Polystyrene and its use for separation of isomers - Adiguzel, Aysegul Cigdem; Korkmaz, Burak; Cakar, Fatih; Cankurtaran, Ozlem; Senkal, Bahire Filiz (ELSEVIER, 2022)
In this study, thermodynamic properties, glass transition temperature and isomer separation ability of PVBC (poly (vinyl benzyl chloride)) -Diethanol amine (PVBC-DEA) polymer was investigated by IGC method. For purpose, the retention diagrams were drawn using interactions between PVBC-DEA with selected isomer solvents (i-butyl acetate, n-butyl acetate and t-butyl acetate) at between 85 and 110 degrees C. The glass transition temperature value of the polymer was determined from the retention diagrams as 76 degrees C and the obtained value, it has been understood that this value is compatible with 75.2 degrees C found by differential scanning calorimetry. The selectivity coefficients, alpha, of the isomer solvents were determined for the PVBC-DEA in the infinite dilution, according to the results obtained, it was revealed that the polymer can separate the isomers. The polymer-solvent interaction parameters for Flory-Huggins theory, chi(infinity)(12), and the equation of state theory, chi(12)*, the effective exchange energy parameters, chi(eff), the weight fraction activity coefficient, Omega(infinity)(1), and also the partial molar heat of mixing at infinite dilution of solvent, Delta(H) over bar (infinity)(1), the molar heat of vaporization of solvent, Delta(H) over bar (v), and the partial molar heat of sorption of solvent, Delta(H) over bar (s), were calculated between 85 and 110 degrees C. The obtained results were discussed. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Inverse Gas Chromatography; Thermodynamics; Isomer Selectivity; Polymer Modification; Polystyrene Based Polymer; INVERSE-GAS-CHROMATOGRAPHY; GLASS-TRANSITION TEMPERATURE; INFINITE DILUTION; SURFACE CHARACTERIZATION; SOLUBILITY PARAMETERS; POLYMER; METHACRYLATE); Chemistry; Engineering